Teacher Assistance in The Development of Merdeka Curriculum Learning Devices - Nadya; Hasanah Faiqoh Maulidah; Hasan Baharun; Hefniy Hefniy; Moch Tohet; Abdul Wahid Zaini (Communautaire: Journal of Community Service, 2023)
The main focus of this research is to understand the contributions and challenges faced by educators in designing and using learning tools that are in accordance with the principles carried by the Merdeka Curriculum. This study also aims to identify the challenges faced by teachers in adopting the Merdeka Curriculum. The method used in this research and community service activity is the Participatory Action Research (PAR) method. The PAR method consists of three interconnected words: participation, research, and action. This method involves several data collection techniques, including participatory observation, structured interviews with teachers, focus group discussions, and document analysis related to the Merdeka Curriculum. The data analysis techniques employed in this study involve qualitative methods such as thematic analysis of interviews and content analysis of the curriculum documents. The findings reveal that: (a) The Independent Curriculum shares similarities with the National Curriculum, easing familiarity for teachers despite name changes. (b) Pancasila student character dimensions and new Learning Outcomes are relatively unfamiliar, needing more time for integration into teaching materials. (c) The activity significantly improves teachers' grasp of the Independent Curriculum, simplifying its application in the classroom.